2019
DOI: 10.1038/s41467-019-13067-8
|View full text |Cite
|
Sign up to set email alerts
|

Environmental co-benefits and adverse side-effects of alternative power sector decarbonization strategies

Abstract: A rapid and deep decarbonization of power supply worldwide is required to limit global warming to well below 2 °C. Beyond greenhouse gas emissions, the power sector is also responsible for numerous other environmental impacts. Here we combine scenarios from integrated assessment models with a forward-looking life-cycle assessment to explore how alternative technology choices in power sector decarbonization pathways compare in terms of non-climate environmental impacts at the system level. While all decarboniza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
125
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(130 citation statements)
references
References 77 publications
3
125
0
2
Order By: Relevance
“…For instance, a comprehensive LCA of a range of International Energy Agency (IEA) world electricity supply scenarios indicated that, in broad terms, those scenarios that rely more heavily on renewable technologies do indeed tend to stabilize or even reduce global pollution, but entail larger (and sometimes potentially critical) demand for key materials, noticeably among which is copper [19]. Another recent study, whose scope also extended to the whole world, found that those decarbonization strategies relying heavily on wind and solar technologies are comparatively more effective in reducing human health impacts than those relying on carbon sequestration, while the use of bioenergy in the mix raises concerns in terms of land use and associated ecosystem damage [20]. Pehl et al [21] carried out a thorough life-cycle comparison of all the direct and indirect GHG emissions from various renewable and non-renewable low-carbon technologies, also including seldom-considered factors such as indirect carbon emissions from land use change.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a comprehensive LCA of a range of International Energy Agency (IEA) world electricity supply scenarios indicated that, in broad terms, those scenarios that rely more heavily on renewable technologies do indeed tend to stabilize or even reduce global pollution, but entail larger (and sometimes potentially critical) demand for key materials, noticeably among which is copper [19]. Another recent study, whose scope also extended to the whole world, found that those decarbonization strategies relying heavily on wind and solar technologies are comparatively more effective in reducing human health impacts than those relying on carbon sequestration, while the use of bioenergy in the mix raises concerns in terms of land use and associated ecosystem damage [20]. Pehl et al [21] carried out a thorough life-cycle comparison of all the direct and indirect GHG emissions from various renewable and non-renewable low-carbon technologies, also including seldom-considered factors such as indirect carbon emissions from land use change.…”
Section: Introductionmentioning
confidence: 99%
“…Analyses of the environmental impact of wind power plants have mainly concerned their impact on birds, vibration emissions, noise-both audible and of the infrasound type-as well the impact on the surrounding landscape [3][4][5]. In a wider context, analyses have been conducted on the impact of wind farm lifecycles with the aid of the Life Cycle Assessment (LCA) method, including areas of potential impact on human health, the quality of the natural environment, and natural resources [6][7][8][9]. Analyses have also concerned the impact of the lifecycle of wind power plants on water and soil environment as well as their emissions into the atmosphere [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Energy sector innovation is where most progress is achievable 4 , but since renewable energies currently account for only 17% of global energy consumption 5 , significant production increases must occur to phase out fossil fuel use 6 . However, the production of renewable energies is also material-intensivemuch more so than fossil fuels 7 -meaning that future production will also escalate demand for many metals [8][9][10][11] . It is unlikely that these new demands will be met by diverting use from other sectors or from recycling materials alone 12,13 .…”
mentioning
confidence: 99%